2007
DOI: 10.1093/humrep/dem029
|View full text |Cite
|
Sign up to set email alerts
|

High bone morphogenetic protein-15 level in follicular fluid is associated with high quality oocyte and subsequent embryonic development

Abstract: The present study demonstrates that the BMP-15 level in FF appears to be a potential factor in predicting oocyte quality and subsequent embryo development, and is correlated with E(2) level, which may additionally be a valuable predictor of oocyte fertilization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
91
1
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 118 publications
(98 citation statements)
references
References 33 publications
3
91
1
3
Order By: Relevance
“…The AAT levels in FF were measured by western blotting as described by Wu YT et al [13]. Briefly, 1.0 mL of FF was diluted in PBS and electrophoresed using 12 % sodium dodecylsulfate polyacrylamide gelelectrophoresis (SDS-PAGE).…”
Section: Analysis Of Alpha-1-antitrypsin (Aat) Complement Component mentioning
confidence: 99%
See 1 more Smart Citation
“…The AAT levels in FF were measured by western blotting as described by Wu YT et al [13]. Briefly, 1.0 mL of FF was diluted in PBS and electrophoresed using 12 % sodium dodecylsulfate polyacrylamide gelelectrophoresis (SDS-PAGE).…”
Section: Analysis Of Alpha-1-antitrypsin (Aat) Complement Component mentioning
confidence: 99%
“…The composition of FF might influence and/or be implicated with oocyte quality. Some human FF proteins have been shown to be correlated with oocyte maturation, fertilization outcome and embryo development [13][14][15]. Therefore, identification of specifically altered protein levels in FF during COH cycles might be helpful in determining the influence of COH on follicular and oocyte development, and to predict IVF outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…They compared FF BMP-15 levels of fertilized 60 oocytes with unfertilized 19 oocytes. FF BMP-15 level of fertilized oocytes were significantly higher than that of unfertilized oocytes [6]. Gueripel et al,observed increased BMP-15 immunostaining on ovarian tissue of mouse stimulated with gonadotropins [15].…”
Section: Discussionmentioning
confidence: 97%
“…Effect of AMH and BMP-15 on estradiol and progesteron production in primarycultured human luteinizing granulosa cells was reported [5]. BMP-15 level in follicular fluid has been demonstrated to associate with oocyte and embryo quality [6]. Researchers observed relation among cumulus cell BMP15 expression level and oocyte maturation, fertilization, and embryonic development [7].…”
Section: Introductionmentioning
confidence: 99%
“…6 The analysis of follicular fluid has recently been a matter of interest as a possible predictor of both oocyte developmental competence and the subsequent potential to achieve fertilization and embryo viability. [6][7][8][9][10] Moreover, the content of follicular fluid (FF) may also reflect the circulating biochemical environment and the changes in blood serum.…”
Section: Introductionmentioning
confidence: 99%